Answer:
There are no solutions.
Step-by-step explanation:
Step 1: Simplify both sides of the equation.
2(9x−6)=6(3x−2)+2
(2)(9x)+(2)(−6)=(6)(3x)+(6)(−2)+2(Distribute)
18x+−12=18x+−12+2
18x−12=(18x)+(−12+2)(Combine Like Terms)
18x−12=18x+−10
18x−12=18x−10
Step 2: Subtract 18x from both sides.
18x−12−18x=18x−10−18x
−12=−10
Step 3: Add 12 to both sides.
−12+12=−10+12
0=2
A is the correct answer!!!
Answer: 52%
Step-by-step explanation:
Answer:
16 : 20 = 0,8 = 80%
Step-by-step explanation:
pls make me a brinist
9Step-by-step explanation: